An Investigation Into Relational And Verbal Processes In The Literature Review In View Of Functional Grammar - Nguyễn Thị Phương Thúy (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This paper examined the verbal processes and relational attributive processes in the literature reviews of the academic writing in view of Funtional Grammar. The investigation looked into the semantic-grammatical profile of how verbal and locution structures are constructed in the discipline of Literature review, and saw if there were similarities and/or differences between the most frequent verb processes. The second goal is to investigate the features of relational attributive process in the literature reviews. Based on the framework ofFunctional Grammar, the features of this process were characterized. A combination of research methods of descriptive method, qualitative and quantitative method, contrastive analysis method were employed in this study. The data were extracted from 80 literature reviews from website (www.academypublisher.com). More than 1000 English samples in literature reviews such as sentences containing verbal and relational processes were collected from the literature reviews. In additional, the data were examined with a closer look at the participants of 2 processes such as sayer, verbal processes, Verbiage, Locution, Carrier, Relational Attributive processes and Attributive in the reviews.The study found that there were some common verbal processes and relational attributive processes with various formulas throughout the literature reviews and a range of differences between the participants of 2 kinds of these processes. The findings of this thesis are expected to serve as a foundation for the researcher to put forward some implications for the readers and writers in writing the literature review. In addition, this thesis can be used as a reference for writers, readers or those who are interested in the literature review and can provide them with a better understanding of Functional grammar into the comprehension and writing the literature review.